2019
DOI: 10.4102/sajp.v75i1.933
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction, activity limitations, participation restriction and contextual factors in South African women with pelvic organ prolapse

Abstract: Background Pelvic organ prolapse (POP) is a multifactorial, poorly understood condition impacting quality of life (QOL). The pathology and aetiology might imply population-specific differences in domains of the International Classification of Function, Disability and Health (ICF). There is, however, a lack of research in this regard in South Africa. Objectives To describe the dysfunction, activity limitations, participation restrictions and contextual factors in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
4
15
2
Order By: Relevance
“…The poor physical performance observed in this study was also reported in studies done in other low income countries [ 10 , 11 , 37 ]. A study done in South Africa by Brandt et al 2019 suggested that the poor physical performance in women with POP could be due to chronic pelvic pain caused by stretching and weakening of the pelvic ligaments which makes it difficult for these women to walk, bend and work.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The poor physical performance observed in this study was also reported in studies done in other low income countries [ 10 , 11 , 37 ]. A study done in South Africa by Brandt et al 2019 suggested that the poor physical performance in women with POP could be due to chronic pelvic pain caused by stretching and weakening of the pelvic ligaments which makes it difficult for these women to walk, bend and work.…”
Section: Discussionsupporting
confidence: 87%
“…Women with POP present with a variety of symptoms including urinary, bowel, sexual, and psychological which greatly compromise their quality of life (QOL) [ 6 9 ]. In the advanced stages, POP presents with debilitating physical symptoms like difficulty in walking, sitting and squatting, which negatively impacts the daily economic activities of these women like farming eventually resulting in poverty [ 10 , 11 ]. In addition, women with POP frequently report limitations to their sexual life such as: lack of sexual desire, arousal, orgasm, and pain during intercourse which ultimately leads to loss of sexual interest with some being abandoned by their husbands [ 5 , 7 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…POP is associated with a variety of urinary, bowel, sexual and psychological symptoms, which may signi cantly compromise the quality of life of the patients (7,8). Most women with advanced stages of POP often have symptoms that cause di culty in walking, sitting and squatting, which affects the performance of their daily household work like farming hence reducing their economic productivity (9,10). In addition, women with POP frequently report limitations to their sexual life such as; lack of sexual desire, arousal, orgasm, and pain during intercourse which ultimately leads to loss of sexual interest with some being abandoned by their husbands (6,8,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…We want to highlight some points of the article ‘Dysfunction, activity limitations, participation restriction and contextual factors in South African women with pelvic organ prolapse (POP)’ (Brandt & Janse van Vuuren, 2019 ).…”
mentioning
confidence: 99%